2012
DOI: 10.1080/17429145.2011.650714
|View full text |Cite
|
Sign up to set email alerts
|

Plant–plant–plant communications, mediated by (E)-β-ocimene emitted from transgenic tobacco plants, prime indirect defense responses of lima beans

Abstract: Some volatile organic chemicals (VOCs), such as terpenes, are responsible for communication between plants.We assessed the priming of defense responses in lima bean by exposing the plants to transgenic-plant-volatiles [(E)-b-ocimene] emitted from transgenic tobacco plants (NtOS2). As it was previously shown that the first receiver lima bean plants, which were infested with spider mites after having been exposed to (E)-b-ocimene from NtOS2, were highly induced to emit VOCs, we analyzed the VOCs emitted from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Consistent with this observation, it has previously been shown that tomato exposed to β-ocimene emitted from transgenic tobacco plants proved to be more attractive to A. ervi than control plants, which possibly resulted from the higher emission of volatiles from tomatoes exposed to the β-ocimene emitted from transgenic tobacco plants ( Cascone et al, 2015 ). Similarly, E-β-ocimene emitted from transgenic tobacco plants has also been found to increase the emission of volatiles in lima bean ( Arimura et al, 2012 ). Furthermore, exposure to (Z)-3-hexenol was found to elicit the release of β-ocimene and linalool and enhance the attractiveness of tea geometrid Ectropis obliqua -infested tea plants to Apanteles sp., the main parasitoid wasp of this moth ( Xin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this observation, it has previously been shown that tomato exposed to β-ocimene emitted from transgenic tobacco plants proved to be more attractive to A. ervi than control plants, which possibly resulted from the higher emission of volatiles from tomatoes exposed to the β-ocimene emitted from transgenic tobacco plants ( Cascone et al, 2015 ). Similarly, E-β-ocimene emitted from transgenic tobacco plants has also been found to increase the emission of volatiles in lima bean ( Arimura et al, 2012 ). Furthermore, exposure to (Z)-3-hexenol was found to elicit the release of β-ocimene and linalool and enhance the attractiveness of tea geometrid Ectropis obliqua -infested tea plants to Apanteles sp., the main parasitoid wasp of this moth ( Xin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…As many compounds can be induced in tea plants by attack from different insects, , they are common HIPVs and may exhibit broad-spectrum insect resistance. A common HIPV in tea plants, β-ocimene, has exhibited anti-insect functions in some other plants, such as Chinese cabbage, tomato, and lima bean . However, its anti-insect function and emission pattern in tea plants are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Plants experiencing insect herbivory frequently generate species-specific blends of volatile compounds [94,95], which can influence fitness in neighboring plants [83,96,97]. Plant-derived compounds associated with herbivory include GLVs [4,12,81], shikimate derivatives [13], and terpenes [98]. However, individual compounds within a blend can affect plant defense and priming as much as the blend itself.…”
Section: Discussionmentioning
confidence: 99%